2021
DOI: 10.1001/jamanetworkopen.2021.15687
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Acceptability of a Smoking Cessation Program for Individuals Released From an Urban, Pretrial Jail

Abstract: IMPORTANCE Tobacco use prevalence among individuals involved in the criminal-legal system is 125% higher than that of the general population and leads to high levels of smoking-related morbidity and mortality.OBJECTIVE To examine the acceptability, feasibility, and preliminary clinical outcomes of a smoking cessation intervention for individuals who are incarcerated. DESIGN, SETTING, AND PARTICIPANTS This pilot randomized clinical trial was conducted fromJanuary 2019 to May 2020. Participants were recruited in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…A recent feasibility trial in an urban jail found that nicotine replacement therapy was feasible to initiate and maintain following release, though there were no differences in abstinence rates between the groups that received standard behavioral health education compared with nicotine replacement therapy and counseling. 41 Future work needs to be conducted on how best to improve the transition of healthcare in and out of jail, which are usually short stay facilities, to the community for CVD risk factors and may also require examining how incarceration (movement from the community to the jail) affects these outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…A recent feasibility trial in an urban jail found that nicotine replacement therapy was feasible to initiate and maintain following release, though there were no differences in abstinence rates between the groups that received standard behavioral health education compared with nicotine replacement therapy and counseling. 41 Future work needs to be conducted on how best to improve the transition of healthcare in and out of jail, which are usually short stay facilities, to the community for CVD risk factors and may also require examining how incarceration (movement from the community to the jail) affects these outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Recognizing the significant emotional stressors that can accompany re-entry into society from prison, Richmond et al conducted a randomized control trial of a behavioral intervention with or without nortriptyline for people who were incarcerated in New South Wales but found no difference in abstinence rates between the two groups at any time point post-release ( Richmond et al, 2013 ). Interventions have also begun during incarceration but continued after release ( Winkelman et al, 2021 ). Reviews of relevant literature have concluded that, beyond a small number of promising studies, this area has not received the attention it deserves and needs ( Puljevic & Segan, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Of the total number of studies selected (n = 19), the majority were quantitative studies (12), others were qualitative (2), and the rest were classified with a mixed methodological approach, quantitative and qualitative (5). Regarding the health interventions described in the studies, most (11) were developed in the context of the transition from prison to the community [18][19][20][21][22][23][24][25][26][27][28], two (02) were initiated after people returned to social life [29,30], and six (06) began during incarceration and were continued after arrest [31][32][33][34][35][36].…”
Section: Studies Characterizationmentioning
confidence: 99%